Brand Awareness Measurement of KPR FLPP Among its Target Market in Jakarta - Arianandhika, Muhammad Bian; Hudrasyah, Herry (Journal of Business and Management, 2012)
Brand Awareness Measurement of KPR FLPP Among its Target Market in Jakarta